Assessment of genetic variation among drought tolerant recombinant inbred lines (RILs) of Indian mustard (Brassica juncea L.) - PK Rai,,; Supriya Ambawat,; Neeraj Gurjar,; VV Singh,; Subaran Singh, (Journal of Oilseed Brassica, 2026)
The present study reveals the genetic variation among 225 Recombinant Inbred Lines (RILs) derived fromthe cross Rohini X PBR-97 which were evaluated under normal and water stress conditions. Significantgenetic variation was observed for plant height, main shoot length, fruiting zone length, siliqua length, biologicalyield/plant, harvest index, seed yield/plant, fibre, phenol, days to flowering under normal conditions while plantheight, main shoot length, fruiting zone length, siliqua length, seed/siliqua, harvest index, phenol, days toflowering were found to be significant under drought conditions. Heritability estimates were high (>70%) formain shoot length, siliqua length, seed yield/plant, and phenol content. Seed yield per plant was significantlyand positively correlated with plant height (0.37**), main shoot length (0.19*), fruiting zone length (0.16*),siliqua length (0.19*), seeds/siliquae (0.16*), biological yield per plant (0.45**) and harvest index (0.61**)and negatively correlated with oil content (-0.13), fibre (-0.28**). Further, 25 promising RILs were identifiedbased on seed yield/plant which can further be used in brassica improvement breeding programmes to developdrought tolerant brassica varieties.